Temperature-dependent Optical Properties of AlN Thin Films by Spectroscopy Ellipsometry. (13th February 2017) - Liu, Yao; Ghafari, Ehsan; Jiang, Xiaodong; Feng, Yining; Feng, Zhe Chuan; Ferguson, Ian; Lu, Na
ABSTRACT: In this work, temperature-dependent optical properties of a series of AlN thin films with different thickness are studied by spectroscopic ellipsometry (SE) ranging from 300 to 825K. The fitted refractive index at 300K is in good agreement with the reported by others, which confirms the high accuracy of the optical model used in this work. The degradation of the absorption properties and the decrease of the bandgap become more pronounced with temperature increases above 475K. A larger change of bandgap at elevated temperature is observed for the thinner AlN epi-layer (300nm) than the thicker ones (404nm). This can be attributed to the poor surface morphologies and crystal qualities in the thinner AlN epi-layer.